Perbaikan Sistem Pergudangan di PT. X - Pratama, Otto; Widyadana, I Gede Agus (Jurnal Titra, 2015)
This paper anlayze PT X warehouse system since some problems that are faced by the company such as full capacity warehouse, the absence of a inventory control system, and bad facility layout. The full capacity warehouse problem is solved by using capacity analysis, repayment of raw material analysis, and selling the clothes waste. The improvement of inventory control system is conducted by comparing periodic review system and economic order quantity, while for the raw materials placement problem is solved by grouping the raw material. A periodic review system is simulated to know the number of raw material savings. The simulation result shows that the number of the raw materials can be reduced as much as 7 percent, while the new raw material placement save 42 percent of traveling distance.